Strategi BAZNAS dalam Memberdayakan Ekonomi Kaum Dhuafa melalui Program Zakat Produktif di Kecamatan Malili Kabupaten Luwu Timur - Abdullah Fikri Adnan; Mahmuddin; Muzdalipafah Sahib; Haeruddin (Jurnal Berita Sosial, 2025)
This study aims to explore and determine how BAZNAS’s startegy in empowering the economy of the poor through productive zakat in Malili Subsdistrict, East Luwu Regency. This study has two research questions, namely: 1) The implementation of of productive zakat programs through the economic empowerment of the poor ini Malili Subsdistrict, East Luwu Regency. 2). The impact of productive zakat programs run by BAZNAS’s in improving the economics independence of the poor in Malili Subsdistrict, East Luwu Regency. This study uses a descriptive qualitative method with an empowerment and scienftific approach. Primary data was obtained through observation, interviews with the head of BAZNAS, two BAZNAS employees, two community leaders and six undreprivuleged people who were the beneficiaries of productiv zakat, as well asdirect documentation in the field. Secondary data was obtained through literature in the form of books, journals, internet and other reading sources related to the study. The results of this study indicate that the empowerment of the poor through productive zakat is running well in accordance with its mechanism, namely the collection of zakat from muzakki. Then, the distribution and utilization of zakat to the poor as a form of productive zakat utilization program. To be targeted for BAZNAS productive zakat, mustahik can submit a proposal or BAZNAS itself can go be seen from the increase in business capital income to the increase in the economic independence of the poor. The implications of this research are: 1) the importance of increasing assistance and training for the poor, not only by providing help but also by continuing to provide skills training so that the products sold are more dominant in the line with trends and keep up with the times. 2) The importance of BAZNAS in facilitating business development networks with broader partners. 3) Expanding the target receipients of assistance, not only to poor entrepreneurs, but also to poor widows and orphans whoo may have the potential to run a business but don’t have the capital.